2017
DOI: 10.1098/rsob.170139
|View full text |Cite|
|
Sign up to set email alerts
|

Foxj1a is expressed in ependymal precursors, controls central canal position and is activated in new ependymal cells during regeneration in zebrafish

Abstract: Zebrafish are able to regenerate the spinal cord and recover motor and sensory functions upon severe injury, through the activation of cells located at the ependymal canal. Here, we show that cells surrounding the ependymal canal in the adult zebrafish spinal cord express Foxj1a. We demonstrate that ependymal cells express Foxj1a from their birth in the embryonic neural tube and that Foxj1a activity is required for the final positioning of the ependymal canal. We also show that in response to spinal cord injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 54 publications
3
21
0
Order By: Relevance
“…To build a theoretical model of CSF flow, we quantify essential parameters such as the canal geometry and the local cilia dynamics. The central canal geometry, as estimated by Dextran injections, corresponds to a cylinder ( Figure 2a1, 2a2 ) of diameter 8.9 ± 0.9 μm (129 WT embryos, Figure 2a3 ) with a very small dorsal extension showing low fluorescence level in the uppermost position, as previously observed with antibody staining for tightjunctions 41 . The dynamics of motile cilia in the CC are investigated in 30 hpf Tg(βactin:Arl13bGFP) embryos in which GFP labels all cilia 31,39,42 .…”
Section: Central Canal Geometry and Properties Of The Motile Ciliasupporting
confidence: 70%
“…To build a theoretical model of CSF flow, we quantify essential parameters such as the canal geometry and the local cilia dynamics. The central canal geometry, as estimated by Dextran injections, corresponds to a cylinder ( Figure 2a1, 2a2 ) of diameter 8.9 ± 0.9 μm (129 WT embryos, Figure 2a3 ) with a very small dorsal extension showing low fluorescence level in the uppermost position, as previously observed with antibody staining for tightjunctions 41 . The dynamics of motile cilia in the CC are investigated in 30 hpf Tg(βactin:Arl13bGFP) embryos in which GFP labels all cilia 31,39,42 .…”
Section: Central Canal Geometry and Properties Of The Motile Ciliasupporting
confidence: 70%
“…We have identified two different subpopulations of motile ciliated cells based on the expression pattern of the two Foxj1 orthologs and the analysis of ciliary mutants. Our results obtained with a 0.6kbfoxj1a:gfp and 5.2kbfoxj1a:gfp [ 17 ] transgenic lines demonstrated that these promoter regions are not sufficient to drive the specific expression pattern of foxj1a in the larval brain and suggest that other regulatory elements may be involved in its transcriptional regulation [ 57 ]. Nevertheless, our data revealed that both foxj1a - and foxj1b -positive cells are needed to generate a robust CSF flow in the ventricles.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ratio of highly expressing CSF-cNs (full arrowheads) was significantly increased in scoliotic (but more variably in straight) rpgrip1l ∆/∆ fish. To determine whether increased expression of URP1/2 peptides can trigger scoliosis, we injected a transgenic construct expressing urp2 in foxj1+ cells, lining central nervous system cavities [27], in eggs from rpgrip1l ∆/+ crosses.…”
Section: Upregulation Of Urp Signaling Participates In Scoliosis Onsementioning
confidence: 99%